Role of Lipopolysaccharide in Stimulating Rheumatoid Arthritis Leukocytes to Produce IL-1β in vitro (World Journal of Experimental Biosciences, 2023)
The pro-inflammatory response plays an important role in the pathogenesis of rheumatoid arthritis (RA), which is considered one of the most common autoimmune diseases around the world. The role of lipopolysaccharide (LPS) in stimulating the pro-inflammatory response in patients with RA requires further clarification. The current study aims to determine the role of LPS in stimulating leukocytes in patients with RA to produce interleukin (IL-) 1 beta (β) in vitro. Here, LPS was extracted from Pseudomonas aeruginosa, and used in stimulating the cultures of leukocytes isolated from patients with RA and cultures of leukocytes isolated from healthy control (HC) people with LPS. Two control groups were employed, first, cultures of leukocytes isolated from patients with RA from HC people, and stimulated with phosphate buffer saline (PBS). The level of IL-1β was measured at the protein in supernatants of cell cultures and at the gene expression in leukocytes. The results showed the effect of LPS in stimulating leukocytes of patients with RA and HC people to produce IL-1β higher than the production of IL-1β in cultures of control groups (leukocytes of RA and HC exposed to PBS). The results also showed that leukocytes of patients with RA stimulated with LPS produced IL-1β (in terms of protein production and gene expression) higher than the production of IL-1β by leukocytes isolated from HC people and stimulated with LPS (P<0.05). It can be concluded that LPS stimulates leukocytes in RA patients to produce a high level of IL-1β and that plays a role in pro-inflammatory response in RA.